Gendered translocal connectedness: Rural–urban migration, remittances, and social resilience in Thailand. Issue 4 (23rd January 2020) - Porst, Luise; Sakdapolrak, Patrick
Abstract: Remittances play a central role in debates on migration and development as well as migration as adaptation to climate change. We seek to contribute to the growing body of literature that addresses the role of gender relations for remittance sending and usage. Based on multisited qualitative research on rural–urban migration in Thailand, we apply the concept of translocal social resilience to expound the multilocal and intersectional dimension of remittances and their impact on social resilience. Building on typical constellations of remittance transfer and usage, the paper accentuates how gender, generational relations, and the household's socio‐economic status shape remittance practices and their effects on social resilience across space. We can thus conclude that addressing intersecting socio‐spatial levels and axes of difference enhances the understanding of remittance potentials for resilience, which also enriches research that frames migration as a means of adaptation.